Soil geochemistry on hillslope - Ts.Davaakhuu; A.Orkhonselenge (Geological Issues, 2023)
This study reveals Soil geochemistry of Mt.Ovoot in the northeast of Khangai Mountain Range, Mongolia. This work is mainly focused on natural processes of sediment transportation through surface and subsurface flows in Mt.Ovoot based on movement of microelements with in soil profiles along the mountain slopes and sediment analyses of particle sizes and shapes. The main purpose is (1) to synthesize previous researches on landscape development in Mongolia, (2) to determine the chemical and physical properties of soils, and (3) analyzing hill slope process soil geochemistry and explain process. During the measurement, two gullies were observed on the lower slope, which occupy area of 9.6 hectares. Movement of the microelements and sediment analyses show intensive slope processes in the Mt.Ovoot. Each surface soil on upper slope contains microelements less than those on lower slope of the mountain, where sediments have been more round and finer. Besides, trace elements of hill slope geochemistry analyzed that modified by anthropogenic towards the hill slope in Mt. Ovoot.